Analisis Gaya Bahasa Pada Album Lagu Mustache And Beard Yang Berjudul ”Manusiaku Manusiamu Manusianya” Sebagai Rekomendasi Materi Bahan Ajar Pembelajaran Puisi Siswa Kelas X - Alensyah, Ade Rama Akbar; Nurhasanah, Een; Syafroni, Roni Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the meaning of the language styles contained in the album "Manusiaku Humanmu Humannya" and to determine the form of teaching materials as recommendations for poetry learning for class X students. This type of research is qualitative research. This research approach uses a stylistic approach that focuses on the meaning of the Mustache and Beard song album entitled "Manusiaku Humanmu Humannya". This research method uses descriptive analysis methods. The subject of this research uses 8 songs which are the best works on the album. This research instrument uses tables with a structured data format. Based on research results from the analysis of the album, the song "Manusiaku Humanmu Humanmu" produces 39 language styles. Consisting of 3 hyperboles, 4 metaphors, 9 personifications, 5 similes, 6 allegories, 6 euphemisms, 5 symbolic ones, and 1 repetition. The language style that is widely used is personification and the language style that is least used is repetition. . Then use it as a recommendation for teaching materials in the form of audio visuals for class X students' poetry learning.